Effect of hydraulic retention time on the denitrification performance and metabolic mechanism of a multi-chambered bio-electrochemical system. (1st December 2021) - Deng, Qiujin; Su, Chengyuan; Chen, Zhengpeng; Gong, Tong; Lu, Xinya; Chen, Zhuxin; Lin, Xiangfeng
Abstract: The effects of hydraulic retention time (HRT) on the denitrification performance of the multi-chambered bio-electrochemistry system and the metabolic mechanism of the microbial community were investigated. Results indicated that the NO3 − -N and NO2 − -N removal efficiency was up to 99.5% and 99.9%, respectively. The electricity generation performance of the system was optimum at 24 h HRT, with the maximum power density and output voltage of the fourth chamber to be 471.2 mW/m 3 and 602.4 mV, respectively. With the decrease of HRT from 24 h to 8 h, the protein-like substance in extracellular polymeric substance (EPS) of granular sludge was reduced and the fluorescence intensities were weakened. Besides, the abundance of metabolism pathway was the highest at 50.0% and 49.9%, respectively, and the methane metabolism (1.8% and 2.0%, respectively) and the nitrogen metabolism (0.8% and 0.9%, respectively) in Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway played important roles in providing guaranteed stability and efficient removal of organic matter and nitrogen from the system. Graphical abstract: Image 1 Highlights: Removal rate of NO3 − -N reached to 99% at 12 h HRT in the system. Electricity generation performance of the system was optimum at 24 h HRT. Protein-like substances in EPS of sludge reduced with the decreasing of HRT. KEGG predicted the metabolism pathway of the system at various HRT.